The Ontology Project for Interactive Digital Narrative - Haahr, Mads (Springer, 2015)
Interactive Digital Narrative (IDN) is an interdisciplinary field in which long established perspectives (literature studies, narratology, oral storytelling practices) and newer views (computer science, communication and digital media studies, artificial intelligence) intersect. This variety of traditions creates difficulties for the exchange between researchers originating in different fields. While some common terms have emerged, a richer shared vocabulary would provide great benefits for the field. However, it is crucial for new vocabulary to be widely accepted. Consequently, we propose a community effort to develop an IDN ontology, inspired by similar efforts in game ontology.
LNCS 9445: Interactive Storytelling
Keywords: Narrative Ontologies; Interactive Digital Narrative; Interactive Digital Storytelling; Narrative Analysis; Narrative Categories; Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities